What are we to understand Gracia to mean? : realist challenges to metaphysical neutralism - Delfino, Robert A.; Gracia, Jorge J. E. (Value inquiry book series ;, 2006)
This book provides a series of challenges to Jorge J.E. Gracia's views on metaphysics and categories made by realist philosophers in the Aristotelian and Thomistic traditions. Inclusion of Gracia's responses to his critics makes this book a useful companion to Gracia's Metaphysics and its Task: The Search for the Categorial Foundation of Knowledge ."A valuable contribution to current metaphysics. The studies of Gracia's important book Metaphysics and its Task are insightful, and his replies to them are meticulous. One of the many merits of the book is the respect evident throughout for the es.